The epidemiological changes of HCV and HBV infections in the era of new antiviral therapies and the anti-HBV vaccine - Cristina Stasi; Caterina Silvestri; Fabio Voller; Francesco Cipriani (Elsevier, 2016)
Summary: The World Health Organization (WHO) resolution adopted in 2010 recognized viral hepatitis as a global health problem. In April 2014, for the first time, the WHO produced guidelines for the screening, care and treatment of persons with hepatitis C infections. In May 2014, a follow-up resolution urged WHO Member States to develop and implement a national strategy for the prevention, diagnosis and treatment of viral hepatitis based on the local epidemiological context. Although blood donor screening, which began in the early 1990s, has reduced the spread of the virus in the population, the WHO estimates that 150 million people are chronically infected with hepatitis C virus (HCV) and are at an increased risk of developing liver cirrhosis and hepatocellular carcinoma. In addition, 3-4 million people are infected each year. HCV treatment is currently evolving rapidly, and several drugs are in various stages of development.With regard to the hepatitis B virus (HBV), in March 2015, the WHO published the first guidelines for the prevention, care and treatment of persons with chronic hepatitis B infection, which were designed to complement the recent guidelines on HCV. Although the introduction of an effective vaccine against the hepatitis B virus has reduced the prevalence and health and economic impact of hepatitis in industrialized countries, the WHO estimates that more than 2 billion people are HBV-infected and 350 million people are chronic carriers. Keywords: Epidemiology, Hepatitis B virus, Hepatitis C virus, Acute viral hepatitis, Chronic liver disease